Engagement of lymphoma T cell receptors causes accelerated growth and the secretion of an NK cell-inhibitory factor - Dubois, Sigrid (Cell Immunol, 2020)
The development of T cell lymphomas in mice that constitutively express a single T cell receptor is surveilled by the action of NK cells. We investigated the effects of engaging the lymphoma TCR in this mouse model. We stimulated lymphoma cells expressing an ovalbumin-specific TCR in vivo using listeria monocytogenes as a vehicle. Infections with listeria expressing ovalbumin but not with control bacteria caused a stable change in lymphoma cells that allowed its growth in mice with normal NK cells. TCR engagement furthermore enhanced lymphoma growth in NK-cell-depleted mice suggesting a lymphoma-intrinsic change that lead to accelerated growth. The ability to grow in mice without prior NK cell depletion did not appear to be accompanied by changes in the recognition of lymphoma by NK cells. Rather, lymphoma immunization was associated with a decrease in NK cell numbers: Leukemic phases were observed for all mice starting three to eight weeks after immunizations, and leukemias were succeeded by the disappearance of NK cells from blood. We also observed strong decreases of NK cell numbers in spleens at the time of death. Co-culture experiments showed decreases in the ability of NK cells to proliferate in response to IL-15 when post-immunization lymphoma cells were present in a mechanism that did not require direct cell contact. Together these data suggest that TCR engagement caused intrinsic changes in T cell lymphoma cells resulting in both accelerated in vivo growth and in the secretion of a factor that caused NK cell disappearance.